1981
DOI: 10.1093/ajcn/34.8.1496
|View full text |Cite
|
Sign up to set email alerts
|

Carnitine deficiency induced during hemodialysis and hyperlipidemia: effect of replacement therapy

Abstract: Plasma carnitine levels were studied in 14 uremic patients before, during, and after hemodialysis. The predialysis plasma carnitine levels were normal but fell during dialysis (half-life of 3.6 h). Plasma carnitine levels rose quickly in the first 6 h after dialysis, after which time the rise was more gradual. Muscle carnitine was significantly reduced in the dialyzed patients (p less than 0.005) compared with controls. In four patients lipid droplets were observed in muscle. Ten patients on maintenance hemodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0
2

Year Published

1983
1983
1998
1998

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 12 publications
6
37
0
2
Order By: Relevance
“…These results are in agreement with some previously published data in the literature [11][12][13][14][15][16][17][18][19][20]. Even though the time-dependent change in serum triglycerides cannot be securely excluded in some of the patients, this decrease should be due to the carnitine-induced stimulation of the oxidation of long-chain fatty acids, which in turn leads to a decrease of their availability for esterification to triglycerides [9,10].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are in agreement with some previously published data in the literature [11][12][13][14][15][16][17][18][19][20]. Even though the time-dependent change in serum triglycerides cannot be securely excluded in some of the patients, this decrease should be due to the carnitine-induced stimulation of the oxidation of long-chain fatty acids, which in turn leads to a decrease of their availability for esterification to triglycerides [9,10].…”
Section: Discussionsupporting
confidence: 91%
“…Carnitine, which is considered to be essential for the transport of fatty acids from the cytosol into the mitochondria, where they are oxidized, seems to play an important role in lipid catabolism [9,10]. However, the results of studies in which L-carnitine has been administered in hemodialysis patients in an attempt to correct the lipid abnormalities are inconclusive, with some studies noting an improvement [11][12][13][14][15][16][17][18][19][20], while others found no change or even an exacerbation of hypertriglyceridemia [14,[20][21][22][23][24][25][26][27][28]. Some of the observed discrepancies might be attributed to differences in racial or ethnic background, cultural factors, diets or to differences in the criteria for selection of the study participants.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, several authors observed predialysis plasma carnitine levels in patients on HD which are not different from the mean of normal controls [14][15][16][17][18] or even significantly elevated [19. 20].…”
Section: Discussionmentioning
confidence: 99%
“…Marked depletion of blood carnitine has been reported during HD [2. [13][14][15][17][18][19][20][21][22][23], TC decreased from 48.2 ± 18.8 to 20.9 ± 9.0, FC from 29.6 ± 12.6 to 9.4 ± 5.6. SCC from 17.7 ± 8.9 to 9.5 ± 5.6 and LCC from 2.5 ± 1.2 to 1.6 ± 0.9 pmol/l [21].…”
Section: Discussionmentioning
confidence: 99%
“…Their uptake into the mitochondria is mediated by the quaternary amine carnitine. Some [39] but not all investigators report low plasma free carnitine in maintenance hemodialyzed patients [40, 41]. Moreover, a deficit in L -carnitine is responsible for atrophy of type I and IIA muscle fibers and is associated with an accumulation of intracytoplasmatic lipids which is not seen in muscular atrophy of the uremic patient [24, 42].…”
Section: Muscle Composition and Metabolism In Uremiamentioning
confidence: 99%